IMPACT OF EARNINGS ANNOUNCEMENTS ON STOCK PRICES – AN EMPIRICAL ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
This study explores the multifaceted impact of earnings announcements on stock prices, drawing on theoretical frameworks, empirical evidence, and practical implications for investors. Earnings announcements play a pivotal role in influencing stock prices by providing critical insights into a company's financial performance and future prospects. The Efficient Market Hypothesis (EMH) posits that stock prices reflect all available information instantaneously, including earnings announcements. Positive earnings surprises, where actual earnings exceed analysts' expectations, typically lead to immediate stock price increases as investors adjust their valuation upwards. Conversely, negative surprises, where earnings fall short of expectations, often result in stock price declines as investors revise their outlook for the company downwards. The magnitude of these price movements can vary based on factors such as market conditions, company size, and the quality of earnings information. Behavioral finance complements the EMH by highlighting market anomalies and psychological biases that influence stock price reactions. The Post-Earnings Announcement Drift (PEAD) phenomenon, for example, suggests that stocks experiencing positive surprises continue to outperform in the subsequent period, indicating a delayed market response to earnings news. Investor sentiment, characterized by tendencies to overreact or underreact to earnings information, further amplifies short-term volatility and price fluctuations. Empirical evidence from event studies consistently demonstrates significant abnormal returns around earnings announcement dates, underscoring the informational content and market impact of these disclosures. Practical implications for investors include the development of trading strategies centered on earnings momentum or contrarian approaches, as well as enhanced risk management practices to navigate heightened volatility during earnings seasons. In conclusion, understanding the impact of earnings announcements on stock prices is essential for investors seeking to capitalize on market inefficiencies, manage risk effectively, and make informed investment decisions aligned with their financial goals. This study provides a foundational overview of the complex dynamics surrounding earnings announcements in financial markets.